Implementation of Corporate Social Responsibility (CSR) and Its Impact on the Company's Financial Performance - Karimah, Naura Firdausi; Sukiswo, Helmy Wahyu (Journal of Economics, Business, and Government Challenges, 2024)
The purpose of this research is to find out how PT Petronika implements Corporate Social Responsibility (CSR) and to identify the impact of CSR programs on the company’s financial performance. The research utilizes qualitative data from two sources: including primary data consisting of interviews, while secondary data consisting of a record of letter disposition and PT Petronika’s financial reports. This study used semi-structured interview methods, observation, and documentation in its data collection. The test results show that CSR has a positive impact on the PT Petronika’s financial statements, which is reflected in an increase in sales that affects the level of profit.